Style inwestowania jako kryterium klasyfikacji funduszy inwestycyjnych - Zamojska-Adamczak, Anna (Application of Investing Styles in Classification of Mutual Funds, 2005)
Mutual funds operating on die capital market in Poland can be classified basing on classical criteria of decision making process such as: risk and return, published output, investing horizon or simplicity of transactions. Widely known in literature classification of mutual funds is based on the type of investment or on risk measures (estimated linear regressions of returns). W.F. Sharpe proposed classification of funds with respect to styles of investment. The style of investment is a method of investment selected by the fund. It lets allows to group funds in particular type with respect to such characteristics as: the goal of investing plan, type of securities creating portfolio, expected return, level of the risk, size and financial condition of fund, preferences, etc.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (12); 2005; nr 1076, s. 134-141